Digitizing Beckett - Van Hulle, D (Cambridge University Press, 2019)
In the “Proteus” episode of Joyce’s Ulysses, Stephen Dedalus famously ruminates on the ineluctable modality of the visible and the audible, mentioning the notions of the “nebeneinander” [side by side] and the “nacheinander” [one after the other] Joyce’s source was probably Otto Weininger, who may, in his turn, be alluding to Lessing’s Laocoon.Lessing’s distinction between the Nacheinander of poetry and the Nebeneinander of visual arts was challenged in Joyce’s last work, Finnegans Wake.